(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
Poisoning is one of the leading causes of morbidity and mortality in both developed and developing countries. Therefore, knowledge of socio-demographic profile of poisoning cases in a region is helpful in prevention and management of poisoning cases evaluate socio-demographic pattern of poisoning cases in Ajmer region of Rajasthan. The present prospective cross-sectional study was conducted in Department of Forensic Medicine and Toxicology, JLN Medical College, Ajmer, Rajasthan, during period of 1 year (January 2016–December 2016). During this period, a total of 82 cases of suspected poisoning related deaths were autopsied. Suspected poisoning cases accounted for 8.02% of total autopsy performed during study period. About 73.2% of the cases were male with male to female ratio 2.73:1. Peak incidence was observed in age group 21–30 years. Maximum cases (75/82) noted among Hindu community. Majority of victims were married and belonged to rural areas. In 35.2% cases, poison was consumed during evening time. Home was place of exposure in 60% cases. In majority of cases, suicide was manner of death. Route of exposure was oral in 87.8% cases. Maximum cases were happened during summer season. Stomach mucosa was congested in majority cases. Organophosphate compounds (51.21%) were the most common poison detected on chemical analysis of viscera. In this study, chemical analysis report of viscera was available in all cases of suspected poisoning. This differentiates this study from most of the contemporary studies related to poisoning.